2009
DOI: 10.1002/ctpp.200910060
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Zeptosecond Electromagnetic Pulses by Electrons Under their Interaction with Femtosecond Laser Pulses

Abstract: The motions of electrons driven by the fields of relativistically intense laser pulses are analyzed for the linear polarization. The treatment is based on the numerical solution of the relativistic Newton's equation with the Lorentz force for laser beams with Gaussian transverse intensity distribution. The electromagnetic radiation of an electron interacting with a laser pulse is also studied. It is shown that: laser fields accelerate electrons both in the transverse and longitudinal directions and the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The great advantage of the classical approach is that calculations can be carried out quite easily, even for an arbitrary space and time dependent laser field. For this reason, the classical approach is extensively used in plasma physics and also in the context of ultra-short pulse generation [39][40][41][42][43][44]. Even though Thomson theory has some important shortcomings.…”
Section: Synthesis Of Short Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The great advantage of the classical approach is that calculations can be carried out quite easily, even for an arbitrary space and time dependent laser field. For this reason, the classical approach is extensively used in plasma physics and also in the context of ultra-short pulse generation [39][40][41][42][43][44]. Even though Thomson theory has some important shortcomings.…”
Section: Synthesis Of Short Pulsesmentioning
confidence: 99%
“…In this paper, we shall study the important role played by the global phase of probability amplitudes in nonlinear Compton scattering [16,17] and its classical approximation -nonlinear Thomson scattering [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. For the classical theory we discuss the conditions of its applicability.…”
Section: Introductionmentioning
confidence: 99%
“…7. It was shown that an electron located far in front of the focus, after interaction, moves in the direction of negative z.…”
Section: Expressions For Energy and Angular Spectra Of Acceleratmentioning
confidence: 98%
“…[65,66]). For instance, the problem of generation of zeptosecond (or even yoctosecond) pulses is currently vigorously studied (see, e.g., [67][68][69][70][71][72][73] and references therein). We have shown, however, that quantum effects prohibit in general the generation of such extremely short pulses of radiation and, in some cases, lead to contradictions with the classical expectations [74].…”
Section: Total Energy Of Generated Radiationmentioning
confidence: 99%